Harmful factors at the workplace of an operating nurse - Tomaszewska, Katarzyna; Majchrowicz, Bożena (Journal of Education, Health and Sport, 2022)
Abstract Introduction: Operating theatre is a very specific work environment. The staff employed in this organizational unit, apart from specific professional qualifications, must have the ability to make quick decisions as well as the skills to utilize highly specialized medical apparatus and equipment. Operating theatre nurses are exposed to various harmful factors, thus strain resulting from this type of work can be both mental and physical. The aim of this paper was to assess the level of knowledge of surgical nurses about harmful factors at their workstations. Material and methods: The study was performed in a group of 625 nurses working in different types of operating rooms of public hospitals in Poland. An original questionnaire survey was used to characterize the harmful factors occurring at the operating room nurse’s workstation. Results: The results obtained prove that according to the nurses surveyed, the main problem associated with working in the operating theatre is constant exposure to harmful factors that have a significant impact on workload. Conclusions: There are factors identified by the staff at the operating theatre nurse’s workstation that affect the level of strain both physically and mentally. Shaping the right working conditions, affecting the efficiency and safety of employees should be a priority for hospital managers and directors.